Research on a rat model of genotype IV swine hepatitis E virus - Zhijie Jian; Youyou Li; Zhiwen Xu; Jun Zhao; Fengqin Li; Huidan Deng; Xiangang Sun; Ling Zhu (Veterinary Medicine and Science, 2022)
Abstract Background Hepatitis E virus (HEV) is an important zoonotic pathogen, Genotypes 3 and 4 are the main zoonotic genotype. Due to the lack of mature and effective culture cell lines, researches on genotype IV swine HEV (SHEV‐4) infection and pathogenic mechanism have been carried out in pigs, gerbils and non‐human primate models. Objectives The aim of this study was to establish a rat infection model by intra‐peritoneal infection with SHEV‐4, which provided a new research idea and scientific basis for further revealing the mechanism of HEV infection and preventing HEV infection. Methods SHEV‐4 virus was administered intra‐peritoneally to 6‐ to 8‐week‐old mice to observe the serological changes and virus release. Results According to the results of the rat serum HEV IgG, ALT and AST levels, swine HEV, minus‐strand HEV RNA can infect Sprague–Dawley rats across species, and there are no obvious clinical symptoms after infection. HEV RNA was detected in most tissues and organs after infection, but the viral load was low. The liver had pathological changes of chronic hepatitis. Conclusions We found that the rat model of porcine HEV infection is a small animal model suitable for the study of HEV infection.